PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP MINAT DAN MOTIVASI BELAJAR SISWA PADA MATERI FUNGSI MENU DAN IKON APLIKASI PEMBUAT GRAFIS DI KELAS XII SMA NEGERI 1 JAWAI - Suryadi Suryadi (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2022)
The purpose of this study was to determine the effect of the Project-Based Learning Model on Students' Interest and Learning Motivation in the Material of Menu Functions and Graphic Maker Application Icons in Class XII SMA Negeri 1 Jawai. The method used in this study is a quantitative research method in the form of experimental research. The technique used to collect data in this study is an indirect communication technique, while the tool used to collect data in this study is a questionnaire. The population in this study were all class XII students of SMA Negeri 1 Jawai in the 2018/2019 academic year with a sampling technique using purposive sampling. The data analysis technique in this study was the first to use a simple linear regression formula, and multiple linear regression. The result that is known after conducting this research is that students' interest in learning for the subjects of menu functions and graphic maker application icons in class XII SMA Negeri 1 Jawai is in the category of a high tendency level of 34.29%. Then the second, the students' learning motivation for the subjects of menu functions and graphic maker application icons in class XII of SMA Negeri 1 Jawai is in the category of a very high tendency level of 62.86%. Furthermore, there is the influence of laboratory facilities on student learning outcomes in the class X simulation and digital communication subjects at SMK Negeri 1 Putussibau with an 18.8% influence percentage. There is an influence of the learning environment on student learning outcomes in the class X simulation and digital communication subjects at SMK Negeri 1 Putussibau with an influence percentage of 24.7%, and finally there is the influence of laboratory facilities and the learning environment together on student learning outcomes. on the subject of simulation and digital communication class X at SMK Negeri 1 Putussibau with the percentage of influence of 34.8%.